RANCANG BANGUN SISTEM ELEKTROPORATOR UNTUK ALAT PASTEURISASI SUSU MENGGUNAKAN PULSED ELECTRIC FIELD - Zuhal Azmiy Dwi Rachman; Ponco Siwindarto; n/a Wijono (Jurnal Mahasiswa TEUB, 2022)
Milk is a highly nutritious food ingredient because fresh milk contains a variety of complete and balanced food substances such as protein, fat, carbohydrates, minerals, and vitamins. Dairy products that have high nutritional value can easily become a place for the development of microorganisms. Microorganisms that breed in milk can cause changes in the color, aroma, and taste of the milk, eventually spoiling the milk. Pasteurization of milk used in the dairy industry uses the LTST (Low Temperature Long Time) and HTST (High Temperature Short Time) methods. Pasteurization by heating milk can reduce the nutritional content of milk. Pulse Electric Field (PEF) is a non-thermal food processing method that provides electric shocks in the form of high-voltage pulses to foodstuffs for a certain time at room temperature. In this study, the design of an electroporator system for milk pasteurization using PEF was carried out. The results of the pasteurization process using an electroporator are considered to be able to reduce the amount of bacteria contained in milk. The highest field strength produced by this tool is able to touch the figure of 32 kV/cm with a maximum voltage of 48 kV. By setting the pump motor duty cycle of 14% and the pasteurization time of 3 minutes, the milk condition has a longer shelf life than unpasteurized fresh milk. These results are evidenced by the methylene blue reductase test in milk, where 100 ml of milk is homogenized with 1 ml of methylene blue and then waited until the milk turns white. Keywords: Milk, Pasteurization, PEF, Duty Cycle, Methylene Blue, Reductase